Filipino Nurse Researchers’ Knowledge, perception, and attitudes toward ChatGPT and Their Research Productivity: A Descriptive Correlation Study - Tuppal, Cyruz P.; Ninobla, Marina Magnolia G.; Loresco, Richard D.; Cabradilla, Mara R.; Tuppal, Shanine Mae P.; Pellacoeur, Leah Kalayaan A.; Roa, Mary Nellie T.; Chan, Judith Mary Ann R.; Panes, Iril I.; Ferreras, Ana Libabel U. (IJERI: International Journal of Educational Research and Innovation, 2025)
Understanding how nurse researchers perceive and utilize this technology offers insights into its integration within the nursing education system in the Philippines and globally, The study described Filipino nurse researchers’ knowledge, perception, and attitudes toward ChatGPT and research productivity. Using a descriptive correlational design, self-made, validated, and piloted questionnaires were sent to three hundred seventy Filipino nurse researchers, both novice (<5 years of research experience) and seasoned (> 10 years of experience). Descriptive statistics were used for profile characteristics, while an independent sample t-test was used to identify significant differences between the two groups of participants in KPA and research productivity. Pearson’s product-moment correlation and a standard linear regression analysis examined the relationship between the independent (KPA) and dependent (research productivity) variables. The level of statistical significance was set at p < 0.05. The largest participant group comprised female Filipino nurse researchers aged 20-30 with Master’s degrees in Nursing. They reported having less than 10 years of experience as instructors and having published 1-5 research articles. The KPA scores indicated a general understanding of ChatGPT’s capabilities, as a valuable tool for research and positive regard toward its use. The study findings further revealed that the t-test did not show a statistically significant difference in perception (t=1.28, p=0.20) and research productivity (t=1.28, p=0,20). But knowledge (t=4.73, p=0.00) and attitude (t=1.28,p=0.02) were found to be significant. Further analysis revealed an adjusted R-square of .145, indicating that the independent variables (knowledge, perception, and attitude) can explain approximately 14.5% of the variance in research productivity. A statistically significant positive correlation was found between attitudes toward ChatGPT and research productivity (β = 0.141, p = 0.012). This study comprised female instructors aged 20-30 with Master’s degrees in Nursing and less than 10 years of experience. They reported having 1-5 publications, suggesting moderate research activity. While the findings revealed a general understanding of ChatGPT’s potential for research, participants hesitated to integrate its use due to ethical concerns, which need further education on the responsible use of ChatGPT in research. Moreover, study findings suggest that Filipino nurse researchers who are more open to using ChatGPT tend to demonstrate greater research output.